1976
DOI: 10.1063/1.322564
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of layer thicknesses and refractive indices in high-energy ion-implanted GaAs and GaP

Abstract: Near normal incidence reflection and transmission measurements of GaAs and GaP samples implanted with large doses of ∼3-MeV ions of 31P+ or 14N+ showed frequency-dependent maxima and minima in the frequency range 800≲ν≲7500 cm−1. Assuming a layer model for the implanted material and considering reflections from layers surfaces, the interference fringes are analyzed to obtain the refractive index and thickness of both the cover and buried layers and substrate. With the same layer model the changes in the GaAs r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This approach was also employed in an ellipsometry measurement of the damage profile ofP+ -implanted material where a transition layer was taken into account. 29 A third possibility for the (7 T values observed here is that the interface is not planar and that (7 T reflects the variation in depth over the area measured by the infrared beam (about 10-1 cm 2 ). While this latter effect might make some contribution, it is unlikely to be a dominant factor because both (7 T and (7 D become less than the minimum detectable value after the shortest annealing time employed.…”
Section: B the Transition Regionsmentioning
confidence: 85%
“…This approach was also employed in an ellipsometry measurement of the damage profile ofP+ -implanted material where a transition layer was taken into account. 29 A third possibility for the (7 T values observed here is that the interface is not planar and that (7 T reflects the variation in depth over the area measured by the infrared beam (about 10-1 cm 2 ). While this latter effect might make some contribution, it is unlikely to be a dominant factor because both (7 T and (7 D become less than the minimum detectable value after the shortest annealing time employed.…”
Section: B the Transition Regionsmentioning
confidence: 85%
“…It was demonstrated that observed interference spectra could be simulated very accurately by such models, provided that a sufficient number of features were incorporated to adequately approximate the physical situation (2,3). Such models gave good nonlinear least square theoretical fits to the measured reflection spectra for a wide range of as-implanted, as well as annealed samples (2)(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 88%
“…In recent years there has been a number of investigations employing optical techniques to characterize materials which were ion implanted (2)(3)(4)(5)(6)(7)(8)(9). One of the techniques frequently used is based on interference effects observed for reflection from a crystalline sample in which a damaged layer was produced by implantation.…”
mentioning
confidence: 99%
“…5), where a square sine function at a spatial frequency Δk k 2ω − 2k ω 2n 2ω − n ω ω∕c is expected in the direction z of the incident plane wave [24,26]. The incident electric field is polarized along a 111 axis, and the following parameters are used: λ 2πc∕ω 5 μm, n 2 ω ε GaAs ω11.01, n 2 2ω ε GaAs 2ω 11.19 [27] and χ 2 2∕ 3 p × 370 pm∕V (for polarization along the 111 axis) [24]. The thickness of the crystal is equal to three times the coherence length L coh π∕Δk, and both faces have an anti-reflective coating at ω and 2ω, giving…”
Section: A Maker Fringesmentioning
confidence: 99%